2005
DOI: 10.1007/s00216-005-3336-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization kinetics of trifloxystrobin

Abstract: The photoisomerization kinetics of trifloxystrobin (TFS) in acetone under artificial sunlight is reported. HPLC analysis showed the TFS, a strobilurine fungicide of EE conformation, was converted into an equilibrium mixture of four isomers after illumination for 7 h. The isomers were identified as EZ, EE, ZZ, and ZE and were separated in the crystalline form by preparative HPLC and characterized by use of a variety of spectroscopic techniques. The quantum yield and reaction constants for the isomerization reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The four TFS geometric isomers transformed into the four corresponding acid. It was consistent with the hydrolytic results and the results of Banerjee et al 7,8 . It is noted that the rate constant was greater than the sum of both hydrolysis and photolysis rate constants (Table-3 It was concluded that the hydrolysis reduced the concentration of the four ester geometric isomers and he isomerization of TFS-EE was accelerated by this hydrolysis.…”
Section: Photolysis Of Trifloxystrobin In Different Ph Bufferssupporting
confidence: 93%
See 1 more Smart Citation
“…The four TFS geometric isomers transformed into the four corresponding acid. It was consistent with the hydrolytic results and the results of Banerjee et al 7,8 . It is noted that the rate constant was greater than the sum of both hydrolysis and photolysis rate constants (Table-3 It was concluded that the hydrolysis reduced the concentration of the four ester geometric isomers and he isomerization of TFS-EE was accelerated by this hydrolysis.…”
Section: Photolysis Of Trifloxystrobin In Different Ph Bufferssupporting
confidence: 93%
“…geometrical isomers of EE, EZ, ZE and ZZ based the connected group arrangement of the two N=C double bonds. Banerjee et al 7,8 built the photoisomerization kinetics of trifloxystrobin in acetone and found it might convert to four geometricals isomers in artificial sunlight under laboratory conditions. The isomerization reached equilibrium after 7 h. They also isolated ZZ, EZ, ZE isomer crystalline form and reported the X-ray crystallographic structures of them [9][10][11] .…”
mentioning
confidence: 99%
“…Figure 1 shows the mass spectrums of TEB (MW 307.8), TFS (MW 408.4) and TFA (MW 394.3) standards. The mass spectroscopic data of TFS and TFA have been discussed in the literatures (Banerjee et al ., 2005, 2007). In this paper, the mass spectrum of TFS also showed typical fragment ion peaks of m/z 116 ([C 8 H 6 N] + ), 131 ([C 8 H 5 NO] + ), 132 ([C 8 H 6 NO] + ), 186 ([MC 11 H 12 NO 4 ] + ), 206 ([MC 9 H 7 NOF 3 ] + ) and 222 ([MC 9 H 7 NF 3 ] + ).…”
Section: Resultsmentioning
confidence: 99%
“…Included in these compounds were three Pathogen Box compounds from the kinetoplastid category: bitertanol ( 1 , MMV688942, T. cruzi ), difenoconazole ( 2 , MMV688943, T. cruzi ) and trifloxystrobin ( 3 , MMV688754, P. falciparum ). Trifloxystrobin is a broad‐spectrum antifungal, whose EE isomer is responsible for biological activity . The 1,2,4‐triazoles 1 and 2 are both known antifungal pesticides, which, like the more popular 1,2,4‐triazole antifungals fluconazole ( 4 ) and posaconazole ( 5 , MMV688774), inhibit CYP51 in the sterol biosynthesis pathway.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%